Apartment ownership around the world: Focusing on credible outcomes rather than ideal systems. (February 2020) - Easthope, Hazel; van den Nouwelant, Ryan; Thompson, Sian
Highlights: Attempts to create typologies for different forms of apartment ownership are challenging because each system differs in practice due to context. Similar systems of ownership can result in different outcomes in practice, and different legal systems can result in similar outcomes. The relationship between legal systems of ownership and owners' experiences is mediated by social, cultural, economic and political context. This has implications for the success of policy mobilities in systems of apartment ownership. Abstract: No matter where in the world they live, if a person lives in a city it is increasingly likely that, if they can buy a property, it will be an apartment. Yet the documents a Sydney buyer's lawyer will review will be different to those in New York or Helsinki because there are many different systems of multi-owned property ownership around the world. These differ because of underlying differences in property law, but also because different jurisdictions have dealt with the dual challenges of horizontal subdivision and cooperative management in very different ways. While creating typologies for these different systems is helpful to understand the varied forms they can take, typologies are challenged by the fact each system differs in practice. In this paper, we draw on Ho's (2014) 'credibility thesis' to explain why it is so difficult to classify multi-owned property systems across jurisdictions. We demonstrate that similar legal systems of multi-owned property can result in different outcomes for owners in practice, just as different legal systems can result in similar outcomes. This is because the relationship between legal systems of ownership and the experiences of owners is mediated by local social, cultural, economic and political contexts.